PERSINGGUNGAN HUKUM ISLAM DAN HUKUM ADAT PADA NASKAH UNDANG-UNDANG SULTAN ADAM KERAJAAN BANJAR (IAIN Tulungagung, 2022)
This paper attempts to analyze the point of intersection of Islamic Law and Customary Law in the Manuscript of the Sultan Adam Act (UUSA) of the Kingdom of Banjar. How do scholars take advantage of one of the characteristics of Islamic law, namely the ability to adapt (legal adaptability) to other laws, supported by one rule from the five major principles in the science of ushul fiqh, namely al-'adah al-muhakkamah which means that customs can be used as a legal basis . Then Ibn al-Qayyim also introduced the rule of taghayyur al-fatwa bi taghayyur al-azminah, which means changes to fatwas due to changes in time, further strengthening the flexibility of Islamic law. This research uses the method of library research or library research, with descriptive analytic. By taking examples of cases from several sections of the Sultan Adam Law, it is found that the meeting between Islamic law and customary law can be seen in these laws filling each other, complementing each other and not giving the impression of tension.